Dept. of Mathematics, S. V. University, Tirupati, Andhra Pradesh, India (International Journal of Engineering and Computer Science, 2013)
This paper aims to describe a method of designing a state vector to place the poles of the characteristic equation of the closed loop of the speed transfer function of the DC motor. The method uses the open loop of the speed transfer function or its controllable canonical form to compare it with the desired closed loop transfer function. The desired characteristic equation of the closed loop is specified by a desired damping ratio and natural frequency.